THE IMPORTANCE OF NOTE-TAKING IN CONSECUTIVE INTERPRETING (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Note-taking in consecutive interpretation (CI) is a distinct form of note-taking, as it involves selectively recording information while multitasking under time constraints during a CI speech segment. These notes are then used to help the interpreter quickly recall the entire source speech. Unlike simultaneous translation, where real-time interpretation requires immediate verbal output, consecutive translation allows interpreters to take short breaks between segments of speech. During these pauses, interpreters rely on notes to recall key information, structure their translations, and maintain coherence. Effective note-taking aids in the retention of complex concepts, proper nouns, numbers, and idiomatic expressions, and serves as a memory aid to prevent loss of meaning. This paper examines note-taking in consecutive interpretation as a key aspect or primary challenge of the consecutive interpreting process.